2016
DOI: 10.1016/j.ympev.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

From the mountains to the coast and back again: Ancient biogeography in a radiation of short-range endemic harvestmen from California

Abstract: The harvestmen genus Calicina is represented by 25 short-range endemic species occurring in the western Sierra Nevada, Transverse and Coast Ranges of California. Our principal aim was to reconstruct the temporal and spatial biogeographic history of this arachnid lineage. We inferred a time-calibrated species tree for 21 of 25 described Calicina species using multiple genes and multilocus coalescent-based methods. This species tree was used as a framework for algorithmic biogeographic and divergence time analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…First, the Papadopoulou et al (2010) rates result in date estimates that coincide with important biogeographic events in the region (see Discussion). Second, various temporal analyses conducted by Emata and Hedin (2016) for the California phalangodid genus Calicina also showed that the Papadopoulou et al (2010) rate provided biologically realistic dates for a California taxon, while slower rates suggested unrealistically old divergence dates. Finally, we note that recent studies of Sclerobunus using whole genome SNP data (Derkarabetian et al 2016) provide younger divergence ages than previously hypothesized in that system, suggesting that the Derkarabetian et al (2010) COI rate may have been underestimated.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…First, the Papadopoulou et al (2010) rates result in date estimates that coincide with important biogeographic events in the region (see Discussion). Second, various temporal analyses conducted by Emata and Hedin (2016) for the California phalangodid genus Calicina also showed that the Papadopoulou et al (2010) rate provided biologically realistic dates for a California taxon, while slower rates suggested unrealistically old divergence dates. Finally, we note that recent studies of Sclerobunus using whole genome SNP data (Derkarabetian et al 2016) provide younger divergence ages than previously hypothesized in that system, suggesting that the Derkarabetian et al (2010) COI rate may have been underestimated.…”
Section: Resultsmentioning
confidence: 98%
“…With two newly described species, Sitalcina now includes a dozen species, and we expect future research to uncover additional undescribed taxa. Ultimately, we predict that Sitalcina diversity might approach that observed in the phalangodid genus Calicina , a taxon that includes over 25 short-range endemic species from central and northern California (Ubick and Briggs 1989, Emata and Hedin 2016). …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations